Pengaruh Limbah Beton sebagai Pengganti Agregat Kasar terhadap Kuat Tekan Beton - Maulana Ishaq; Rita Nasmirayanti; Asri Yuda Trinanda (Civil Engineering Collaboration, 2021)
Concrete is the main material factor in a construction project field that is often used, because concrete has a high compressive strength value so it is very useful for structural buildings to withstand axial forces or compressive forces on the building itself where the structure can be used. for the long term. However, along with the increase in construction development in Indonesia, it has a negative impact on the environment around the construction site because with the rampant construction of this building it will trigger environmental pollution due to the remaining concrete waste from the construction project. On this basis, it encourages the author to conduct research by utilizing waste concrete as a substitute for coarse aggregate for the compressive strength of concrete, by reusing the concrete waste will increase the life of the material from the waste itself. In this study, the materials used were tested first, such as; cement density, silt content, water content, specific gravity absorption, wear testing and sieve analysis on aggregates. Then for the concrete mixture using concrete waste with variations of 0%, 25%, 50%, 75% and 100% of the total weight of coarse aggregate. In this study, the compressive strength at the age of 21 days with a mixture of 0%, 25%, 50%, 75%, and 100% concrete had a compressive strength of 200.92 kg/cm2, 188.83 kg/cm2, 206, respectively. 96 kg/cm2, 177.50 kg/cm2, and 179.01 kg/cm2. Then experienced an average shrinkage of 9.53 kg/cm2 at the age of 28 days. The optimum compressive strength is at 50% mixed variation, with a value of 206.96 kg/cm2 because it has an increase of 3% higher than normal concrete compressive strength with a mixing ratio of 1:2.5:3.5 and a slump value of ±13.25 cm and the dry weight of the concrete is 7.69 kg.